FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK ASURANSI JIWA SYARIAH (STUDI KASUS PT. ASURANSI JIWA SYARIAH BUMIPUTERA 1912 CABANG MEDAN) - Kahfita Ardana; Fauzi Arif Lubis; Reni Ria Armayani Hasibuan (EKSYA : Jurnal Ekonomi Syariah, 2023)
This study aims to explain the factors that influence consumer behavior towards the decision to purchase sharia life insurance at Bumiputera Sharia Life Insurance. The research method used is a quantitative method. By collecting data using a Likert scale model questionnaire taken from a sample of 95 respondents. In processing research data using the SPSS Release 26.0 For Windows application. Based on the results of the analysis that has been done, the regression equation Y = 0.135 + 0.216+0,294 + 0,309 + 0.197 + e. From the results of statistical analysis it is known that there is a positive and significant effect partially that the four independent variables have a significant effect on the dependent variable. The value of the cultural variable is 2.294, the social variable is 3.058, the personal variable is 2.980, and the psychological variable is 2.339. Then the value >value is 1.98667. Based on the simultaneous F test, the value was 42.994 > 2.47 and a significant 0.000 <0.05. The results of the R correlation test obtained an R value of 0.810, so the R correlation between X and Y variables has a very strong relationship. While the value is 0.656, meaning that 65.6% of purchasing decisions are influenced by cultural factors, social factors, personal factors, and psychological factors, while the remaining 34.4% are influenced by other variables outside this study.